Magnetite Functionalized on Graphene Nanoplatelets Surface as Radar Absorbing Matrix in X-Band Region - Krisman Hans Tunggul Purba; Andri Hardiansyah; M. Zuhnir Piliang; Anisa Salsabila; Bintang Dwi Nur Rohmad; Riri Murniati (Indonesian Journal of Chemical Studies, 2026)
The development of radar absorbing materials (RAM) is a crucial factor in advancing stealth technology, particularly in aerospace and defense sectors. In this study, a nanocomposite consisting of graphene nanoplatelets (GNP) and Ferrous-Ferric Oxide (Fe3O4 ) was successfully synthesized through a mechanical homogenization process using Planetary Ball Milling (PBM). This method was selected to ensure uniform dispersion of the magnetic Fe3O4 particles within the conductive GNP matrix, aiming to combine their respective magnetic and dielectric loss mechanisms for enhanced microwave absorption. Surface morphology observations revealed that Fe3O4 nanoparticles were homogeneously embedded on the wrinkled surface of the GNP layers, forming a well-integrated nanostructure. X-ray diffraction analysis confirmed that the Fe3O4 maintained its characteristic spinel cubic structure following synthesis. The composite exhibited a noticeable reduction in crystallite size and overall crystallinity, which is attributed to the mechanical impact during milling and the disordered nature of GNP. These structural modifications facilitate enhanced multiple scattering and interfacial polarization, which contribute to microwave attenuation. The electromagnetic absorbing performance showed that the GNP/Fe3O4 nanocomposite achieved a maximum reflection loss (RL) of –13.9 dB at 11.46 GHz with optimal absorber thicknesses of 3 mm and 5 mm. Additionally, the composite exhibited a high absorption efficiency of 99.48% (based on through power calculation), indicating excellent performance in the X-band frequency range. Overall, the results suggest that this GNP/Fe3O4 nanocomposite offers promising potential as a lightweight, cost-effective, and efficient RAM for stealth technology.